Rapid-sequence MRI for long-term surveillance for paraganglioma and phaeochromocytoma in patients with succinate dehydrogenase mutations. Issue 6 (December 2016) - Daniel, Eleni; Jones, Robert; Bull, Matthew; Newell-Price, John
Abstract : Background: Patients with SDHx mutations need long-term radiological surveillance for the development of paragangliomas and phaeochromocytomas, but no longitudinal data exist. The aim of the study was to assess the performance of rapid-sequence non-contrast magnetic resonance imaging (MRI) in the long-term monitoring of patients with SDHx mutations. Methods: Retrospective study between 2005 and 2015 at a University Hospital and regional endocrine genetics referral centre. Clinical and imaging data of 47 patients with SDHx mutations ( SDHB (36), SDHC (6) and SDHD (5)) who had surveillance for detection of paragangliomas by rapid-sequence non-contrast MRI (base of skull to pubic symphysis) were collected. Results: Twelve index cases (nine SDHB, one SDHC and two SDHD ) and 35 mutation-positive relatives were monitored for a mean of 6.4 years (range 3.1–10.0 years). Mean age at the end of the study: SDHB 46.9 ± 17.6 years; SDHC 42.3 ± 24.4 years; SDHD 54.9 ± 10.6 years. On excluding imaging at initial diagnosis of index cases, 42 patients underwent 116 rapid-sequence MRI scans: 83 scans were negative and 31 scans were positive for sPGL/HNPGL in 13 patients. Most patients had multiple scans ( n = number of patients (number of rapid-sequence MRI scans during screening)): n = 9 (2), n = 20 (3), n = 6 (4), n = 1 (6). Nine patients (three index) were diagnosed with new paragangliomas during surveillance and non-operated tumour size was monitored in nine patients. There were two false-positive scans (1.6%). Scans were repeated every 27 ± 9 months. Conclusions: Biannual rapid-sequence non-contrast MRI is effective to monitor patients with SDHx mutations for detection of new tumours and monitoring of known tumours.